OPTIMIZATION OF REGIONAL ASSETS IN KUANTAN SINGINGI REGENCY (KUANSING HOTEL BUILDING STUDY) - Shinta Rohani; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Fixed assets are one of the elements that must be managed properly in order to produce reliable information in the regional financial reports. However, it is still found that management of regional assets is not well done by the Government so that it can raise problems. One of them is the Kuansing Hotel.This study examines how to optimize regional asset Management in Kuantan Singingi Regency on the procurement and construction of the Kuansing Hotel and analyze the factors of its avoidance. Research uses a type of qualitative descriptive research, which is a problem solving procedure by exposing the data, then analyzed and interpreted by giving conclusions.  The data collection uses interviews, field observations, and library studies that aim to describe (descriptive) and explain (explanatory or confirmatory) to the phenomenon occurring.Based on the research done was obtained by return that the regional asset management in Kuantan Singingi District still not optimal. Found inhibiting factor in optimizing regional asset Management in Kuantan District in the procurement and development of Kuansing Hotel, the asset has not been well-established assets, HR understanding is still minimal, technical support users not Optimal, difficulty supporting Data when needed, Data that is not stored, and the lack of socialization of asset management regulations.Keywords: optimization, management, assets